The effect of sexual counseling on depression, anxiety, stress, sexual knowledge and sexual quality of life in men who have undergone invasive coronary interventions: An RCT - Seyyed Mohsen Sadatinejad; Alireza Farokhian; Mohsen Taghadosi; Seyed Gholamabbas Mosavi (International Journal of Reproductive BioMedicine, 2021)
Abstract Background: Sexual dysfunctions are common in men with ischemic heart disease, especially in men undergoing therapeutic interventions. Objective: This study intended to assess the effect of counseling on depression, anxiety, stress, sexual knowledge and sexual quality of life in men after invasive coronary interventions in the post catheterization department of Kashan Shahid Beheshti Hospital during 2018. Materials and Methods: The study population consisted of 54 male participants who had undergone an invasive coronary intervention. The intervention group received counseling and the control group underwent the standard ward routine. Data were collected using the depression anxiety stress scales, Abraham's sexual quality of life, and the Yi-Hung Sexual Knowledge questionnaires before discharge and also two months later. Results: Within two months, the intervention group's mean score of sexual knowledge significantly increased, compared with the control group, from 12.37 to 14.81 (p ≤ 0.001). The intervention group's mean score of sexual quality of life also significantly increased, compared with the control group, from 48.2 to 60.7 (p ≤ 0.001). Moreover, the mean anxiety score changed in the intervention group from 11.18 to 5.25, again a significant difference compared with the control group (p = 0.01). But, the differences in the depression and stress scores were not significant. Conclusion: Our findings suggest that sexual counseling may improve sexual knowledge, sexual quality of life and anxiety in men following invasive coronary intervention, but might not reduce their stress or depression. Further studies are needed to confirm these findings.